2015
DOI: 10.4149/neo_2015_077
|View full text |Cite
|
Sign up to set email alerts
|

Association between computed tomography-detected calcification and thyroid carcinoma

Abstract: This study aimed to investigate the diagnostic value of calcification detected by computed tomography (CT) for the differentiation of benign and malignant thyroid nodules. This is a retrospective study of 930 consecutive patients (709 women, 221 men; mean age 51 years) with pathologically proven thyroid nodules. The characteristics of calcification on CT images were correlated with the pathological results. A total of 168 patients were pathologically diagnosed with thyroid carcinomas and 762 patients with beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The agreement between US and pathologic analysis was significantly higher than that between CT and pathologic analysis. The inferiority of CT for identification of calcifications may be due to its inability of identifying calcifications that are less than 1 mm in size 4. Kim13 also found that CT was inferior to US for detecting microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agreement between US and pathologic analysis was significantly higher than that between CT and pathologic analysis. The inferiority of CT for identification of calcifications may be due to its inability of identifying calcifications that are less than 1 mm in size 4. Kim13 also found that CT was inferior to US for detecting microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
“…However, these calcifications found on preoperative US are often missed or invisible on CT of the neck in the same patient 5,13. The incidence of calcifications detected by US is reported to be approximately 34.3% to 53.5%,7,8,10,13,19 which is higher than that for CT, which is reported to be approximately 24.8% to 35.2% 4,5,13…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Calcification is a common phenomenon in both benign and malignant thyroid nodules, 15 , 16 and the incidence of calcification in malignant nodules is higher. 17 , 18 Many studies have assessed various calcifications for their diagnostic value in benign and malignant nodules. 5 , 10 , 15 18 Solitary calcified thyroid nodules are examples of single coarse calcifications without visualization of the surrounding low-density focus whose density is lower than the normal thyroid gland tissue.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Many studies have assessed various calcifications for their diagnostic value in benign and malignant nodules. 5 , 10 , 15 18 Solitary calcified thyroid nodules are examples of single coarse calcifications without visualization of the surrounding low-density focus whose density is lower than the normal thyroid gland tissue. 17 Kwak et al 19 reported that cases that show solitary calcified nodules without soft tissue involvement can be diagnosed as thyroid papillary carcinoma on ultrasound, and Ma and Li 20 also showed that malignant pathology was present in 40% of five cases on ultrasound.…”
Section: Introductionmentioning
confidence: 99%